Foundational Investigation of an Acoustic Sensor for the Detection of Lumps in 2d Breast of Lactating Mother - Mohamad Zalani, Afiq Humaidi; Mohd Muji, Siti Zarina (Evolution in Electrical and Electronic Engineering, 2024)
Lactation refers to the process of producing and secreting milk from the mammary glands, typically occurring in mammals, including humans. There are some diseases that relate to breastfeeding, such as mastitis, blocked milk duct, nipple pain, and low milk supply. This project aims to investigate of breast lumps in lactating mothers by using Comsol Multiphysics 6.1. An acoustic sensor is a suitable sensor that can sense blocked ducts in mammary glands. This project model the anatomy of the breast in 2D geometries that involves creating and defining the spatial structures that represent the physical system of the breast in real life. The 2D model of a breast with lump milk surrounded by an acoustic sensor is being simulated. Two configurations of sensors are being investigated, two and four sensors. For each of the sensor configurations, four types of milk are being investigated, which are 37% of solid milk, 49.5% of solid milk, 59.6% of solid milk, and 72.4% of solid milk. The findings from this study will aid in determining whether the mother has a milk lump or not. The result shows that the more solid milk exist at the breast, the less acoustic and voltage received at the acoustic receiver. It also reveals that the low frequency penetrates more to the milk lump which result on higher acoustic received by the receiver. The results demonstrate a promising future for acoustic sensors in sense lump milk, although further investigation is necessary to explore different acoustic sensor arrangements and counts in real-world implementation.